2018
DOI: 10.1016/j.anifeedsci.2017.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Lambs fed cassava silage with added tamarind residue: Silage quality, intake, digestibility, nitrogen balance, growth performance and carcass quality

Abstract: A B S T R A C TThe objective of this study was to evaluate the effects adding tamarind residue to cassava silage on the quality of the silage and its in vitro ruminal fermentation, as well as the growth performance and carcass quality of lambs. A completely randomized design with four inclusion levels (0.00, 100, 200 and 300 g/kg) of tamarind residue (Tamarindus indica L.) added to cassava silage was used. Twenty mini-silos were used to prepare samples of the four treatments (five replicates each), which were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 37 publications
0
4
0
3
Order By: Relevance
“…We infer that the greater flow of nutrients ingested by these animals contributed to the deposition of tissue—mainly muscle (see increased REA)—resulting in larger carcasses. Souza et al (2018) also observed a linear increase in the weight of the hot carcass and in the REA of sheep with the inclusion of tamarind residue in the silage of the cassava shoot part. The increase observed in the carcass weight was also reflected in the positive linear behavior of the weight of the leg and palette of the sheep due to the inclusion of DCBM.…”
Section: Discussionmentioning
confidence: 88%
“…We infer that the greater flow of nutrients ingested by these animals contributed to the deposition of tissue—mainly muscle (see increased REA)—resulting in larger carcasses. Souza et al (2018) also observed a linear increase in the weight of the hot carcass and in the REA of sheep with the inclusion of tamarind residue in the silage of the cassava shoot part. The increase observed in the carcass weight was also reflected in the positive linear behavior of the weight of the leg and palette of the sheep due to the inclusion of DCBM.…”
Section: Discussionmentioning
confidence: 88%
“…The pulp of this fruit is though edible, it is still considered as an industrial waste in countries where it is grown abundantly (Galvao et al 2019). The dry matter of pulp generated during processing of this fruit is about 50 to 65% and comprised of modest amount of crude protein (74.8 g/kg), neutral detergent bre (609g/kg), non-berous carbohydrate (268 g/kg) in addition to lignin (185 g/kg) and tannin (75 g/kg) as reported (Santos et al 2018;Souza et al 2018). Despite a number of valuable phytoconstituents and properties of Tamarind pulp, there is scant scienti c information on its application in broiler production and health under heat stress.…”
Section: Introductionmentioning
confidence: 93%
“…De acordo Gandra et al (2018), que ao trabalharem com adição de quitosana na silagem com aditivo antimicrobial, observaram aumento nas perdas por gases e inferiram que esta perda está relacionada com o aumento da presença dos microrganismos. Souza et al (2018) confrontaram a redução do pH da silagem com o teor de carboidratos não fibrosos, observando aumento nas perdas por gases das silagens estudadas. É evidente que as perdas que ocorrem por meio da produção de gases são influenciadas por diversos fatores no processo da ensilagem.…”
Section: Perda Por Gasesunclassified